WITHDRAWN: Adult hippocampal neurogenesis and antidepressants effects. (February 2020) - Planchez, Barbara; Surget, Alexandre; Belzung, Catherine
Abstract : The Publisher regrets that this article is an accidental duplication of an article that has already been published in Current Opinion in Pharmacology, 50 (2020), 88–95, https://doi.org/10.1016/j.coph.2019.11.009 . The duplicate article has therefore been withdrawn.